Welfare regimes and social workers' conceptions of social problems and professional roles: - a comparative study of Chile, Ireland, Lithuania and Sweden (Journal of Comparative Social Work, 2023)
This article compares social work in countries representing four different welfare regimes: Chile, the Republic of Ireland (refer to elsewhere as ‘Ireland’), Lithuania and Sweden. The aim is to examine how social workers in different contexts refer to families’ complex needs, how contextual factors influence social workers’ positions and actions, and how they make sense of their work. Social workers in 15 focus groups, 4 per country except for Chile with 3, were interviewed about their conceptions of ‘family’, ‘families with complex needs’, and reasoning about interventions in relation to a fictitious complex case vignette. The understanding of complex needs appears relatively individualized in Chile and Lithuania, while contextual factors were more pronounced in the Irish and Swedish material. Chile, exemplifying a familialized family policy regime, reflects a poverty-compensatory social worker role that also supports familial reproduction; Ireland, a partly de-familialized regime, reflects a supportive and risk-reactive role; Lithuania, a re-familialized regime reflects a patriarchal risk-reducing role and Sweden, a de-familialized policy regime, reflects a rights-oriented and technocratic role. Welfare regimes shape different social work practice contexts. However, to some extent, social workers around the world share a common work ethos in how they, for the best interest of the people they work with, deal with the cross-pressure from social problems and political-ideological priorities.